On system with distributed shared memory - Hovhannes Z. Nalbandyan (Изд-во НАН РА)
Distributed shared memory systems combine the scalability of loosely coupled multiple computer systems with the ease of usability of tightly coupled multiprocessors, providing with transparent replication and caching of data. This paper introduces distributed system for parallel computing { DSPC, that provides distributed shared memory on top of network of workstations. Programming model, memory organization, cache-coherence protocol and adaptive techniques are discussed in the paper. An evaluation with some well-known DSM benchmarks was done to present the overall performance of the DSPC system.
Keywords: Mathematics